2015
DOI: 10.1590/0034-7167.2015680517i
|View full text |Cite
|
Sign up to set email alerts
|

Family participation to elderly rehabilitation with femoral fracture

Abstract: How to cite this article: Avila MAG, Pereira GJC, Bocchi SCM. Family participation to elderly rehabilitation with femoral fracture.Rev Bras Enferm. 2015;68(5):601-7. DOI: http://dx.doi.org/10.1590/0034-7167.2015680517iSubmission: 12-15-2014 Approval: 07-13-2015 ABSTRACT Objective: verify if the mode of care adopted by caregivers favored functional independence recovery by elderly with and without the presence of nervous system disease and mental and behavioral disorders; and, if disease interfered with their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…The occurrence of falls followed by proximal femoral fracture occurred predominantly in women (67.4%), corroborating national [25][26][27] and international [5,28] studies. Research conducted in 131 public hospitals in Spain that included 56,500 patients ≥ 60 years, hospitalized for proximal femoral fractures, during the period 2002-2005, showed that 78.5% of the fractures occurred in women [5], rates higher than those found in this study (67.4%).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The occurrence of falls followed by proximal femoral fracture occurred predominantly in women (67.4%), corroborating national [25][26][27] and international [5,28] studies. Research conducted in 131 public hospitals in Spain that included 56,500 patients ≥ 60 years, hospitalized for proximal femoral fractures, during the period 2002-2005, showed that 78.5% of the fractures occurred in women [5], rates higher than those found in this study (67.4%).…”
Section: Discussionsupporting
confidence: 78%
“…The literature indicates that unmarried individuals were more likely to fall when living alone [9,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerando o intenso envelhecimento populacio nal, a elevada incidência de quedas em idosos é contexto promissor às FFP com consequente acometimento de sua independência funcional. Na maioria das vezes, a reabilitação demanda novo arranjo familiar em atendimento às necessidades do idoso (7)(8) . O grande desafio dos profissionais de saúde é fazer com que o idoso retorne às condições pré-cirurgia, e a recuperação da sua independência funcional e qualidade de vida passa a ser um desafio também para os seus familiares.…”
unclassified